Surveillance for Azole-Resistant Aspergillus fumigatus in a Centralized Diagnostic Mycology Service, London, United Kingdom, 1998–2017 - Abdolrasouli, Alireza; Petrou, Michael A.; Park, Hyun; Rhodes, Johanna L.; Rawson, Timothy M.; Moore, Luke S. P.; Donaldson, Hugo; Holmes, Alison H.; Fisher, Matthew C.; Armstrong-James, Darius (Frontiers in Microbiology, 2018)
Background/objectives: Aspergillus fumigatus is the leading cause of invasive aspergillosis. Treatment is hindered by the emergence of resistance to triazole antimycotic agents. Here, we present the prevalence of triazole resistance among clinical isolates at a major centralized medical mycology laboratory in London, United Kingdom, in the period 1998 – 2017. Methods: A large number (n = 1469) of clinical A. fumigatus isolates from unselected clinical specimens were identified and their susceptibility against three triazoles, amphotericin B and three echinocandin agents was carried out. All isolates were identified phenotypically and antifungal susceptibility testing was carried out by using a standard broth microdilution method. Results: Retrospective surveillance (1998-2011) shows 5/1151 (0.43%) isolates were resistant to at least one of the clinically used triazole antifungal agents. Prospective surveillance (2015-2017) shows 7/356 (2.2%) isolates were resistant to at least one triazole antifungals demonstrating an increase in incidence of triazole-resistant A. fumigatus in our laboratory. Among five isolates collected from 2015 to 2017 and available for molecular testing, three harboured TR34/L98H alteration in the cyp51A gene that are associated with the acquisition of resistance in the non-patient environment. Conclusions: These data show that historically low prevalence of azole resistance may be increasing, warranting further surveillance of susceptible patients.